Mycobacterium abscessus: Shapeshifter of the Mycobacterial World - Ryan, Keenan; Byrd, Thomas F. (Frontiers in Microbiology, 2018)
In this review we will focus on unique aspects of Mycobacterium abscess (MABS) which we feel earn it the designation of “shapeshifter of the mycobacterial world”. We will review its emergence as a distinct species, the recognition and description of MABS subspecies which are only now being clearly defined in terms of pathogenicity, its ability to exist in different forms favoring a saprophytic lifestyle or one more suitable to invasion of mammalian hosts, as well as current challenges in terms of antimicrobial therapy and future directions for research. One can see in the various phases of MABS, a species transitioning from a free living saprophyte to a host-adapted pathogen.